2019
DOI: 10.1590/0037-8682-0256-2018
|View full text |Cite
|
Sign up to set email alerts
|

Binational burden of American cutaneous leishmaniasis in Oiapoque, Amapá State, Brazil, bordering French Guiana

Abstract: Introduction: American cutaneous leishmaniasis (ACL) is regarded as a public health problem in the Oiapoque basin, between Brazil and French Guiana. Methods: Data on ACL occurrence/epidemiological profile and etiology were sourced from Brazilian health services and a reference laboratory. Rainfall correlation was also analyzed. Results: Majority of the ACL cases were observed in adult men working as gold miners. ACL incidence peaks appeared to be linked to periods 2 months after the dry season. Migratory flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
3
8
0
1
Order By: Relevance
“…This information, collected on the importance of the influence of human activities in increasing the risk of this disease, as well as the numerous studies carried out on the possible anthropisation of the vector cycle as shown in Colombia [34] and Manaus, Brazil [63], suggest that human activities in the rainforest in the Amazon and French Guiana could promote a peri-domestication of the CL disease cycle. Also, throughout Amazonia, people could be infected in peri-urban forest fragments with great canopy cover, which is essential for maintenance of the Leishmania vector/reservoir species diversity and abundance [6466].…”
Section: Discussionmentioning
confidence: 99%
“…This information, collected on the importance of the influence of human activities in increasing the risk of this disease, as well as the numerous studies carried out on the possible anthropisation of the vector cycle as shown in Colombia [34] and Manaus, Brazil [63], suggest that human activities in the rainforest in the Amazon and French Guiana could promote a peri-domestication of the CL disease cycle. Also, throughout Amazonia, people could be infected in peri-urban forest fragments with great canopy cover, which is essential for maintenance of the Leishmania vector/reservoir species diversity and abundance [6466].…”
Section: Discussionmentioning
confidence: 99%
“…The municipality of Oiapoque (03°49'29"N, 51°49'05"W) is the most important Brazilian socioeconomic link with the bordering Ultramarine Department of French Guiana. ACL is endemic in this region and is regarded as a “bi-national” issue, asapproximately half of cases appear to be acquired on the Brazilian side, and half on the French Guianan side [9]. Two environments were selected to be surveyed, as follows:…”
Section: Methodsmentioning
confidence: 99%
“…braziliensis is considered an emerging cause of ACL; reported to be linked to forest encroachment associated with the gold-mining industry [8]. Epidemiological data on the clinical profile of ACL patients in the Brazilian region revealed sporadic mucosal commitment presumed to be caused by this parasite species, drawing attention to a worrisome public health issue [9].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in rainfall during the dry season has been linked to an increase in CL cases two months later, possibly due to frequent forest activities during the dry months. [10] Only three CL outbreaks have been described in French Guiana so far. Two occurred in military personnel in 1998 [11] and 2002 [12] and a third one in scientists infected with L. braziliensis during a forest trip [13].…”
Section: Introductionmentioning
confidence: 99%